Polyphony in jazz and pop music: aspects of analysis - Onyshchenko, Kateryna; Shabanova, Tetiana (Professional Art Education, 2026)
Object . The article considers the main aspects of the analysis of polyphony in jazz and pop music from the perspective of integrating polyphonic techniques in the formation of trends in modern musical directions. The purpose of the article is to develop the main aspects and prospects of polyphony in jazz and pop music as a musicological and educational process. Methods & methodology. The following methods were used in the study: analytical to establish connections between the components of musical works; comparative to compare works of different styles and genres; historical-dialectical to establish relationships between musical and non-musical factors for the formation of a musical work. Scientific novelty of the article lies in substantiating the importance of including the analysis of polyphonic techniques in jazz and pop music in the musicological and music-educational discourse. Results. It was found that the study of polyphony in contemporary art goes far beyond musicology and has an interdisciplinary nature. It was shown that the analysis of polyphonic components in pop and jazz works has a broad general cultural and ideological and aesthetic context. It was established that the inclusion of analytical tasks in educational components that create an analysis of polyphonic techniques in pop and jazz works allows students to learn to analyze not only purely musical material, but also the connection between non-musical performers and musical means. Conclusions. The study of polyphony outside the academic compositional tradition is necessary, since the process of joint enrichment of two spheres of musical creativity - academic and popular - is in constant development, including in Ukraine. In the music-educational direction, the enrichment of educational courses in music-theoretical disciplines is relevant not only in the practical aspect, but also in the theoretical-analytical aspect. This will contribute to the development of analytical thinking in students through the ability to use a wide range of interdisciplinary communication, which is one of the important professional competencies of a musician.